Kajian Mobil Listrik yang Sesuai dengan Kebutuhan Masyarakat Indonesia - Achmad Risa Harfit; Ahcmad Fauzan (Information Technology and Science (ITScience), 2024)
The development of electric vehicles is one of the government's objectives to save energy and reduce air pollution. The technology for electric vehicles, mainly for personal transportation, involves replacing conventional combustion engines with electric motors. Electric vehicles' advantage lies in eliminating fuel consumption, resulting in nearly zero emissions. To determine the type of electric vehicles that meet the needs of Indonesian society, this study employs the Quality Function Deployment (QFD) method. The research surveyed 40 respondents in the Jabodetabek area to assess their responses to electric vehicle technology in Indonesia. The QFD matrix analysis revealed the priority customer requirements, which include after-sales service availability at every authorized dealer (ATPM), particularly for spare parts and mechanical support, to facilitate vehicle maintenance. The ideal price for electric vehicles is under 300 million IDR. They should have a passenger capacity of seven people and serve multiple functions as family cars, work vehicles, and commercial vehicles. The desired range on a full battery charge is 300 to 500 km, and features such as air conditioning (AC), radio, MP3 players, and comfortable seating are essential. The required motor power ranges from 30kWh to 50kWh.Currently, electric vehicles marketed by several ATPMs in Indonesia still require further development to align with the needs of Indonesian society, ensuring their acceptance in the domestic automotive market.